An Experimental Study on Web Hardening Technology Using Encasement by RPC and Lacing Reinforcement - Bassim Jaffer, Yousif; Alshimmeri, Ahmad Jabbar Hussain (Salehan Institute of Higher Education, 2026)
Over the past ten years, cold-formed steel two-channel sections featuring edge-stiffened castellated cellular web apertures have been developed and are now widely used in New Zealand. Previous research on vertical compression has shown that using edge-stiffened web openings in these channel sections increases their vertical load capacity. Subsequent studies expanded to include hexagram web holes; however, the literature still lacks investigations on the effect of applied vertical pressure on web openings in two-channel sections with perforated webs. This research addresses that gap. The aim of this study is to evaluate the structural response of symmetrical castellated two-channel (2C) sections. Six specimens of castellated 2C beams made of cold-formed steel and encased in reactive powder concrete with diagonal reinforcement on both sides were examined. The concrete encasement and reinforcement enhanced the beam’s resistance to buckling, bending, and both horizontal and vertical shear, and also improved joint performance. Two concentrated loads were applied at the beam center to investigate the structural behavior of each specimen. The results showed that the presence of a joint gap enhanced load resistance. The ultimate load increased by 6.75% compared with the reference specimen SCB2C-rLG20% in G3, by 30.86% compared with SCB2C-rL in G2, and by 1064.73% compared with SCB2C/R1 in G1. The specimen with a 30% gap demonstrated the best load capacity and the highest ductility compared with the reference specimen and the other specimens.